Characterization of individual multifunctional nanoobjects with restricted geometry - Harnagea, C.; Azodi, M.; Nechache, R.; Cojocaru, C.-V.; Buscaglia, V.; Buscaglia, M.T.; Nanni, P.; Rosei, F.; Pignolet, A. (Phase transitions, 2013)
Anisotropic nanostructures such as nanowires (NWs)/nanotubes and nanometer-sized islands are the subject of intense research efforts due to several interesting phenomena observed to occur in confined geometries with a high aspect ratio and/or reduced size. Understanding and controlling the mechanical and electromechanical behaviors of these nanostructures are crucial for the practical implementation of such building blocks as active or passive components in nanodevices. Recent progresses toward the characterization of individual one-dimensional (NWs and nanotubes) and two-dimensional (islands) functional nanoscale objects of piezoelectric and ferroelectric (BaTiO 3 , Bi 4 Ti 3 O 12 (BiT), and NaNbO 3 ) and multiferroics (BiFeO 3 and Bi 2 FeCrO 6 (BFCO)) are presented. These nanoobjects have been characterized using scanning probe microscopy-based techniques, combined with various modulation schemes for enhanced sensing capabilities. The most remarkable results include: ferroelectricity of NaNbO 3 /Nb 2 O 5 nanotube heterostructures, negative piezoelectric coefficient in highly anisotropic BiT mesoscopic rods, and preservation of the multiferroic character of epitaxial BFCO nanoislands.